2019
DOI: 10.15448/2178-3640.2018.2.31948
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Intercultural Competence: CDA of EFL Students’ Baseline Portfolios

Abstract: In monocultural classes, Saudi English as a Foreign Language (EFL) students have to acquire not only linguistic competence but also to develop Intercultural Competence (IC) when they read and write in English. This article investigates IC scattered in EFL students’ baseline portfolios collected in an enrichment critical reading class at the Preparatory Year of Najran University. IC is operationalised as intercultural attitude, intercultural knowledge and intercultural skills evident as discourses in intercultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Compared with the pretreatment findings (Hazaea, 2018), the posttreatment findings showed a high level of self-esteem and appreciation of self and other cultures after introducing the levels of cda. This improvement was manifested in the types of discourses evident in the participants' encounters with written discourse.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Compared with the pretreatment findings (Hazaea, 2018), the posttreatment findings showed a high level of self-esteem and appreciation of self and other cultures after introducing the levels of cda. This improvement was manifested in the types of discourses evident in the participants' encounters with written discourse.…”
Section: Discussionmentioning
confidence: 56%
“…Compared with the pretreatment findings (Hazaea, 2018), the analysis shows that the participants represented a high level of cia at the posttreatment stage. They were able to associate the discourse of food diversity with intercultural competitive discourses.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The tests prove that the observation and interpretation of the research group are important and positive. The findings of this study would help overcome the deficiencies identified in previous intercultural research by Saudi English students (Aldosari, 2013;Fageeh, 2011;Hazaea, 2018;Osman, 2015). During the discovery period, ethnographic techniques such as those proposed in the intercultural program were used to encourage the experimental group to develop ethnographic abilities for the grasp of cultural standards, to reflect on its own society, to communicate cultural distinctions and to understand and explore culture as a target and its potential.…”
Section: Discussionmentioning
confidence: 79%
“…Previous research into the teaching of Saudi English language teaching context has demonstrated concern that existing teaching methods do not encourage intercultural understanding of students and argued in support of more culturally focused approaches and of providing more intercultural teaching materials (Aldosari, 2013;Fageeh, 2011;Hazaea, 2018;Osman, 2015). This concern is not uncommon in the English Department at Najran University.…”
Section: The Studymentioning
confidence: 99%